A Fusion Protein Consisting of the Vaccine Adjuvant Monophosphoryl Lipid A and the Allergen Ovalbumin Boosts Allergen-Specific Th1, Th2, and Th17 Responses In Vitro. (1st June 2016) - Schülke, Stefan; Vogel, Lothar; Junker, Ann-Christine; Hanschmann, Kay-Martin; Flaczyk, Adam; Vieths, Stefan; Scheurer, Stephan
Abstract : Background . The detoxified TLR4-ligand Monophosphoryl Lipid A (MPLA) is the first approved TLR-agonist used as adjuvant in licensed vaccines but has not yet been explored as part of conjugated vaccines. Objective . To investigate the immune-modulating properties of a fusion protein consisting of MPLA and Ovalbumin (MPLA : Ova). Results . MPLA and Ova were chemically coupled by stable carbamate linkage. MPLA : Ova was highly pure without detectable product-related impurities by either noncoupled MPLA or Ova. Light scattering analysis revealed MPLA : Ova to be aggregated. Stimulation of mDC and mDC : DO11.10 CD4 + TC cocultures showed a stronger activation of both mDC and Ova-specific DO11.10 CD4 + TC by MPLA : Ova compared to the mixture of both components. MPLA : Ova induced both strong proinflammatory (IL-1 β, IL-6, and TNF- α ) and anti-inflammatory (IL-10) cytokine responses from mDCs while also boosting allergen-specific Th1, Th2, and Th17 cytokine secretion. Conclusion . Conjugation of MPLA and antigen enhanced the immune response compared to the mixture of both components. Due to the nonbiased boost of Ova-specific Th2 and Th17 responses while also inducing Th1 responses, this fusion protein may not be a suitable vaccine candidate for allergy treatment but may hold potential for the treatment of other diseases that require a strong stimulation of the host's immune system (e.g., cancer).